The journal of law, economics, & organization. (Oxford : Oxford University Press, 1985)
The Journal of Law, Economics, & Organization is an interdisciplinary exercise. It seeks to promote an understanding of many complex phenomena by examining such matters from a combined law, economics, and organization perspective (or a two-way combination thereof).
Description based on online resource; title from home page (viewed on September 28, 2016).
Keywords: Law -- Periodicals; Economics -- Periodicals; Organization -- Periodicals